Problems encountered at the interface between piling and substructure construction - Chew, Danny Poh Huat. (2008)
This report examines the potential disputes and interface problems among piling, excavation and building contractors with implications on the current practice of contracts award in Singapore. Many factors are considered when problems are encountered, the common ones being time, cost and the possible involvement of Third Party liabilities. Very often, inadequacies in the execution of the actual construction work has resulted in major foundation defects and failures. These inadequacies are often overlooked, as contractors usually tend to be more concerned with accumulating savings on cost and time. However these savings would not be justified if substantial rectification works were required to correct the foundation problems. The four case histories in this report will highlight some of these problems.